CORRECTIONAL WORKS WITH MENTALLY DEAD CHILDREN (International journal of artificial intelligence, 2025)
The article describes the main aspects and methods of correctional work with mentally retarded children. Special education methods, psychological-pedagogical approaches and methods of speech and social skills development are analyzed.